2010
DOI: 10.3311/pp.ci.2010-1.03
|View full text |Cite
|
Sign up to set email alerts
|

Concrete strength tendency in the wall of cylindrical spun-cast concrete elements

Abstract: The aim of the research was to characterize the concrete mixtures for spun-cast concrete and to determine the relationship between the compacting ratio and the manner of segregation. In the research 23 specimens of 9 different mixtures with low w/c ratio were tested. Investigated parameters included w/c, spinning speed, duration, and properties of the aggregate. The strength of the concrete in the outer, middle and inner region of the spun-cast element and of the vibrated cube was assessed by testing drilled c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 5 publications
0
22
0
Order By: Relevance
“…Correlations between the strength of the spun-cast and of vibrated elements made of mixtures with low w/c ratio have been published by the authors earlier [16][17][18]. Due to radial segregation the composition of the material and its strength changes throughout the wall of the element.…”
Section: Introductionmentioning
confidence: 96%
See 4 more Smart Citations
“…Correlations between the strength of the spun-cast and of vibrated elements made of mixtures with low w/c ratio have been published by the authors earlier [16][17][18]. Due to radial segregation the composition of the material and its strength changes throughout the wall of the element.…”
Section: Introductionmentioning
confidence: 96%
“…It has been shown that the composition of the material changes throughout the wall of the specimen due to the radial segregation. The incidence of gravel is higher in the outer region because of its higher density [18]. The result of rebound tests strongly depend on the properties of the microenvironment.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations